2021
DOI: 10.1111/cobi.13640
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of ignoring dispersal variation in network models for landscape connectivity

Abstract: Habitat loss and fragmentation can negatively influence population persistence and biodiversity, but the effects can be mitigated if species successfully disperse between isolated habitat patches. Network models are the primary tool for quantifying landscape connectivity, yet in practice, an overly simplistic view of species dispersal is applied. These models often ignore individual variation in dispersal ability under the assumption that all individuals move the same fixed distance with equal probability. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…The lack of dispersal records in some species in our study can be explained by a low number of recaptures (L. boscai) or by their low abundance (H. molleri and D. galganoi), because the number of detected movements is often proportional to population size (Sullivan et al 2021). For these species, reconstructing representative dispersal kernels requires specific surveys focused on their breeding sites and/or longer time series.…”
Section: Photoidentificationmentioning
confidence: 90%
See 1 more Smart Citation
“…The lack of dispersal records in some species in our study can be explained by a low number of recaptures (L. boscai) or by their low abundance (H. molleri and D. galganoi), because the number of detected movements is often proportional to population size (Sullivan et al 2021). For these species, reconstructing representative dispersal kernels requires specific surveys focused on their breeding sites and/or longer time series.…”
Section: Photoidentificationmentioning
confidence: 90%
“…To account for the intraspecific variability in dispersal frequencies and distances, dispersal can be regarded as a probabilistic variable rather than a fixed maximum value when designing a graph (Sullivan et al 2021 ). This method is more biologically realistic, relying on the use of dispersal kernels to estimate dispersal probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the consequences of variation in dispersal is essential to understanding how plants will respond to changing environmental conditions under climate change, habitat fragmentation, and increasing urbanization (Bullock et al, 2017; Sullivan et al, 2021). Yet most mathematical models of dispersal either ignore variation altogether (using mean population estimates of dispersal like dispersal distance or rate) or use a simplistic version of dispersal variation.…”
Section: Dispersal Variation In the Theoretical And Empirical Literaturementioning
confidence: 99%
“…Such simplifications have important implications for the conclusions drawn from models. For example, Sullivan et al (2021) found that ignoring dispersal variation in network models of connectivity in grasslands overestimated a population's resilience to local extinctions and underestimated its resilience to fragmentation. Furthermore, assuming individuals do not disperse beyond the mean dispersal distance ignores the importance of long‐distance dispersal events.…”
Section: Dispersal Variation In the Theoretical And Empirical Literaturementioning
confidence: 99%
“…Propensity to make prospecting EHRMs prior to dispersal may be tied to individual personality (Burkhalter et al, 2015 ; Debeffe et al, 2013 ), so it follows that habitat selection during both prospecting and dispersal EHRMs also may vary by individual (Wey et al, 2015 ). While studies of landscape connectivity attempt to link features and conditions of the environment with animal movement at a population level (Taylor et al, 1993 ; Tischendorf & Fahrig, 2000 ), individual behavioral variation may complicate inference of connectivity (Bélisle, 2005 ; Sullivan et al, 2021 ). Indeed, generalist species typically exhibit greater degrees of behavioral specialization (Bolnick et al, 2003 ; Carlson et al, 2021 ; Woo et al, 2008 ) and thus may adhere less to population‐level patterns of connectivity; additionally, this could be coupled with individual attraction to familiar landscape features (for an example with generalist species [wapiti, Cervus canadensis ] see (Wolf et al, 2009 )).…”
Section: Introductionmentioning
confidence: 99%